18-Year-old patient with Klinefelter syndrome (47, XXY) and complete androgen insensitivity syndrome (CAIS) – case report. (3rd June 2021) - Skalska, Karolina; Ziółkowski, Maciej; Skoczylas, Adrian; Teleon, Marta; Grymowicz, Monika; Pollak, Agnieszka; Smolarczyk, Roman; Płoski, Rafał; Męczekalski, Błażej
Abstract: Aims: The aims of the presented case report are to emphasize the importance of a proper diagnostics and treatment in the case of the coexistence of Klinefelter syndrome (KS, 47 XXY) and complete androgen insensitivity syndrome (CAIS). Since there is no causal treatment it is necessary to provide the patient with a good quality of life, including psychological and sexological support. Materials and methods: The presented case report is the retrospective analysis of the patient's medical history over the 3 years. Results: At the age of 15, the patient was directed to genetic testing due to primary amenorrhea. The results of the patient showed an incorrect male karyotype with the SRY gene present (47, XXY). A molecular diagnostics revealed a very rare variant of the androgen receptor (AR) mutation responsible for tissue insensitivity to androgens. The detected mutation has not been described in the available databases so far. Following a diagnosis of the presence of Klinefelter syndrome (KS, 47 XXY) together with complete androgen insensitivity syndrome (CAIS), the patient underwent a bilateral gonadectomy. Conclusions: In women with KS and CAIS physiological reproduction and maintenance of normal sex, hormone levels are not possible. A gonadectomy is performed due to the risk of malignant testicular tumors.